Errors in organizations - Frese, Michael 1949-; Hofmann, David A. (Psychology Press, 2011)
1. Errors, error taxonomies, error prevention, and error management : laying the groundwork for discussing errors in organizations / David A. Hofmann and Michael Frese -- 2. Learning through errors in training / Nina Keith -- 3. The role of errors in the creative and innovative process / Michelle M. Hammond and James L. Farr -- 4. Revisiting the 'error' in studies of cognitive errors / Shabnam Mousavi and Gerd Gigerenzer -- 5. Collective failure : the emergence, consequences, and management of errors in teams / Bradford S. Bell and Steve W.J. Kozlowski -- 6. Team training as an instructional mechanism to enhance reliability and manage errors / Sallie J. Weaver, Wendy L. Bedwell, and Eduardo Salas -- 7. Learning domains : the importance of work context in organizational learning from error / Lucy H. MacPhail and Amy C. Edmondson -- 8. Errors at the top of the hierarchy / Katsuhiko Shimizu and Michael A. Hitt -- 9. When things go wrong : failures as the flip side of successes / Erik Hollnagel -- 10. The link between organizational errors and adverse consequences : the role of error-correcting and error-amplifying feedback processes / Rangaraj Ramanujam and Paul S. Goodman -- 11. Cultural influences on errors : prevention, detection, and management / Michele J. Gelfand, Michael Frese, and Elizabeth Salmon -- 12. A new look at errors : on errors, error prevention, and error management in organizations / Michael Frese and David A. Hofmann.
Includes bibliographical references and indexes
Keywords: Fehlentscheidung; Irrtum; Organisatorisches Lernen; Fehleranalyse; Organisationsverhalten; Organizational learning; Organizational behavior; Errors; Errors / Research